2007
DOI: 10.1038/sj.bjc.6603575
|View full text |Cite
|
Sign up to set email alerts
|

Strategies for the introduction of human papillomavirus vaccination: modelling the optimum age- and sex-specific pattern of vaccination in Finland

Abstract: Phase III trials have demonstrated the efficacy of human papillomavirus (HPV) vaccines in preventing transient and persistent high-risk (hr) HPV infection and precancerous lesions. A mathematical model of HPV type 16 infection and progression to cervical cancer, parameterised to represent the infection in Finland, was used to explore the optimal age at vaccination and pattern of vaccine introduction. In the long term, the annual proportion of cervical cancer cases prevented is much higher when early adolescent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
60
1
2

Year Published

2007
2007
2013
2013

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(66 citation statements)
references
References 18 publications
3
60
1
2
Order By: Relevance
“…Previous modelling studies have predicted that, if coverage rates are high, vaccination will produce positive herd-immunity effects. 18,19,27 Hence, if high coverage rates are attained (which would be expected in Canada with routine immunization), the population-based number needed to vaccinate will likely be lower than the estimates in our study. On the other hand, if coverage rates are low or if our esti- Canadian data specific to human papillomavirus (HPV) type for infection, cervical intraepithelial neoplasia, cervical cancer and genital warts.…”
Section: Discussioncontrasting
confidence: 44%
See 1 more Smart Citation
“…Previous modelling studies have predicted that, if coverage rates are high, vaccination will produce positive herd-immunity effects. 18,19,27 Hence, if high coverage rates are attained (which would be expected in Canada with routine immunization), the population-based number needed to vaccinate will likely be lower than the estimates in our study. On the other hand, if coverage rates are low or if our esti- Canadian data specific to human papillomavirus (HPV) type for infection, cervical intraepithelial neoplasia, cervical cancer and genital warts.…”
Section: Discussioncontrasting
confidence: 44%
“…These assumptions are based on results from clinical trials that showed that prophylactic HPV vaccines were highly effective for at least 5 years, that there is no evidence of waning efficacy and that the vaccine induces robust immune memory, which is the hallmark of long-term protection. 16,17 Similar to other HPV vaccine modelling studies, [18][19][20][21] we assumed that the duration of vaccine protection in the base case is lifelong. However, given the substantial uncertainty around this parameter, we varied the mean duration of protection between 30 years (assuming vaccine protection wanes at 3% per year) and life (previous antibody decay models, based on trial data for HPV type 16, have predicted that the median duration of detectable vaccineinduced serum anti-HPV-16 levels following vaccination range from 32 years to life…”
Section: Vaccine Characteristicsmentioning
confidence: 99%
“…Extending previous work by others (Hughes et al, 2002;Taira et al, 2004;Elbasha and Galvani, 2005;Barnabas et al, 2006;Dasbach et al, 2006;French et al, 2007), we developed a flexible dynamic model of HPV-16 and -18 sexual transmission between males and females. We linked this model to our stochastic model of cervical carcinogenesis that includes nonvaccine targeted (i.e., non-16, -18) high-and low-risk HPV types to assess the cost-effectiveness of including boys in a pre-adolescent vaccination programme in Brazil.…”
mentioning
confidence: 99%
“…(72) The second model explores the optimal age at vaccination and pattern of vaccine introduction in Finland. (73) The authors find that, once the full impact of vaccination is reached, the annual proportion of HPV type 16-associated cervical cancer cases prevented is expected to be 67% if vaccination of girls occurs at age 15 years, and/or 68% if it occurs at age 12 years, assuming 70% coverage. If vaccination occurs at age 12 years, vaccinating males as well as females is found to prevent an additional 15% of cases annually, if male coverage is 30%.…”
Section: Contribution Of Male Hpv Infection To Female Infection and Dmentioning
confidence: 99%